THE EXAMINING THE CAPITAL STRUCTURE DETERMINANTS: EMPIRICAL ANALYSIS OFREAL ESTATE AND PROPERTY INDUSTRY IN INDONESIA - Hamdi Agustin; Sri Indrastuti; Amries Rusli Tanjung (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This research investigates the effect capital structure on the leverage decision of real estate and Property Company listed on the Indonesia Stock Exchange (IDX) .The population consists of 45 property and Real Estate Company. The study 29 sample because of difficulty in getting the data. The period under study is from 2010 to 2015. The data are taken from property and real estate company annual reports. In this study using panel data and analysis using pooled ordinary least square (OLS).The results showed that all coefficients are significant for LEV variable. The finding showed that TAG variable is inconsistent with the trade-off theory otherwise SIZE variable is consistent with the trade-off theory. ROA has a positive effect on LEV. This indicates that consistent with the pecking order theory. RISK variable is inconsistent with the agency theory.